The dialogue of negation : debates on hegemony in Russia and the West - Lester, Jeremy (London ; Sterling, Va. : Pluto Press, 2000)
Annotation The dialogue between large elements of the Western and the Soviet/Russian left has all too often been one of negation rather than affirmation. The Dialogue of Negation pursues this argument and examines the conceptual and strategic richness of hegemony, providing an overview of the key debates which have shaped its historical development. Jeremy Lester situates the modern evolution of hegemony within an East-West dimension and focuses in particular on the deep-seated difficulties and incompatibilities of much of this interaction. Lester offers a defence of Gramsci's understanding of hegemony as a key element of the revolutionary class struggle. He acknowledges Gramsci's own disputes within the Marxist domain, and celebrates the theoretical and practical legacy he bequeathed to those who continue the struggle to replace capitalism with socialism. Lester provides a critical defence of modernity against the challenge of postmodernity, arguing that it is only within the parameters of modernity that a meaningful form of socialism can succeed. He seeks to highlight the inconsistencies and illogicalities of those theorists who see the transition to some kind of postmodern condition as offering new possibilities for the transcendence of capitalism.
Includes bibliographical references (pages 183-200) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Gramsci, Antonio, -- 1891-1937 -- Contributions in political science; Gramsci, Antonio, -- 1891-1937; Power (Social sciences); Political science -- Philosophy; Pouvoir (Sciences sociales); POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- International Relations -- General; Political science; Political science -- Philosophy; Power (Social sciences)